Performance evaluation of 3-D transforms for medical image compression - Sunder, , R. Shyam; Sriraam,, N; Eswaran,, C. (2005)
In this paper, 3-D discrete Hartley, cosine and Fourier transforms are used for the compression of magnetic resonance images and x-ray angiograms. The performance results are then compared and evaluated. The transforms are applied on image blocks of sizes 8x8xM where M represents the number of slices. The resultant transform coefficients are quantized and then encoded using a combination of run length and Huffman coding schemes to achieve maximum compression. The performances of the transforms are evaluated in terms of peak signal to noise ratio and bit rate. It is found from the experimental results, that 3-D discrete Hartley transform yields the best results for magnetic resonance brain images whereas for x-ray angiograms the 3-D discrete cosine transform is found to be superior to the other two transforms.